2021
DOI: 10.7759/cureus.16588
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Functional Independence Measure Score Prediction After Stroke in Kaifukuki (Convalescent) Rehabilitation Ward Annexed to Acute Care Hospital

Abstract: IntroductionPrediction models of functional independent measure (FIM) score after kaifukuki (convalescent) rehabilitation ward (KRW) are needed to decide the treatment strategies and save medical resources. Statistical models were reported, but their accuracies were not satisfactory. We made such prediction models using the deep learning (DL) framework, Prediction One (Sony Network Communications Inc., Tokyo, Japan). MethodsOf the 559 consecutive stroke patients, 122 patients were transferred to our KRW. We di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Practical examples of the use of Prediction One in financial institutions presented an AUC of 85% or higher [16]. The prediction model in this study had an AUC of 91.7%, which we considered to be highly accurate, similar to previous studies employing Prediction One [13][14][15]. For the cutoff values of the endpoints used to determine walking independence in patients with stroke hospitalized in recovery wards, Kitaji [10] reported that for patients with a first stroke, the berg balance scale (BBS) had an AUC of 97.9% with a cutoff of 45.5 points, and the timed up and go test (TUG) had an AUC of 97.6% with a cutoff of 15.6 seconds in the maximum walking speed condition.…”
Section: Ai-based Prediction Model For Walking Independence Using Pre...supporting
confidence: 81%
See 2 more Smart Citations
“…Practical examples of the use of Prediction One in financial institutions presented an AUC of 85% or higher [16]. The prediction model in this study had an AUC of 91.7%, which we considered to be highly accurate, similar to previous studies employing Prediction One [13][14][15]. For the cutoff values of the endpoints used to determine walking independence in patients with stroke hospitalized in recovery wards, Kitaji [10] reported that for patients with a first stroke, the berg balance scale (BBS) had an AUC of 97.9% with a cutoff of 45.5 points, and the timed up and go test (TUG) had an AUC of 97.6% with a cutoff of 15.6 seconds in the maximum walking speed condition.…”
Section: Ai-based Prediction Model For Walking Independence Using Pre...supporting
confidence: 81%
“…Although the process of building a prediction model is difficult to track because of the nature of machine learning, Prediction One shows the "prediction contribution," which indicates the degree to which each item contributes to the prediction results. In analyses using Prediction One, the coefficient of determination for the model predicting independence at discharge from a recovery unit on admission was 0.972 [13], that for independence at 6 months after surgery in patients with cerebral hemorrhage was 0.997 [14], and that for independence at 6 months after surgery for subarachnoid hemorrhage was 0.994 [15]. All of these models are reportedly highly accurate, and their use in predicting outcomes is highly anticipated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Functional Independence Measure (FIM) is a widely accepted, 18-item motor and cognitive function score that originated from the American Academy of Physical Medicine and Rehabilitation and the American Congress of Rehabilitation Medicine ( 27 , 28 ). The FIM is calculated as a composite score based on direct observation by a multidisciplinary rehabilitation team that documents the patient's disability and level of assistance required to perform activities of daily living ( 29 ). Each motor and cognitive item earns an ordinal numerical score ranging from 1 to 7.…”
Section: Methodsmentioning
confidence: 99%